The Influence of Talent Management And Employer Branding on Employee Retention with Employee Engagement as a Mediating Variable at Prima Inti Medika Hospital North Aceh - Maqfirah, Siti; Majid, M. Shabri Abd.; Putra, Teuku Roli Ilhamsyah (International Journal of Scientific Research and Management (IJSRM), 2024)
The purpose of this study is to examine how talent management and employer branding impact employee retention, focusing on the role of employee engagement. The study involved 168 participants, who were all employees of Prima Inti Medika Hospital in North Aceh. Data was collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS, as well as the Sobel Test. The results indicate that neither talent management nor employer branding directly and significantly affects employee retention. However, both talent management and employer branding do significantly influence employee engagement. Additionally, employee engagement has a noteworthy impact on employee retention. These findings suggest that talent management and employer branding indirectly affect employee retention through their influence on employee engagement. To improve employee retention, it is recommended that the management of Prima Inti Medika Hospital, North Aceh, focuses on promoting positive relationships, mutual support, and motivation among colleagues to enhance performance and reduce turnover intentions.